Botswana : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper suggests that it is essential to save a substantial portion of mineral revenues now to ensure fiscal sustainability for a post-diamond period. Taking the non-mineral primary balance into account can help clarify desirable fiscal policies. Botswana's real effective exchange rate is broadly in line with economic fundamentals and consistent with external sustainability, indicating no threat to external stability. Export performance and other indicators suggest a number of structural competitiveness obstacles that could explain the low labor productivity and poor export and export diversification outcomes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet